2022
DOI: 10.3390/gels8110717
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Sensing Properties of Nb-Doped ITO Thin Films Deposited by the Sol–Gel Method

Abstract: The aim of the present study was the development of Nb-doped ITO thin films for carbon monoxide (CO) sensing applications. The detection of CO is imperious because of its high toxicity, with long-term exposure having a negative impact on human health. Using a feasible sol–gel method, the doped ITO thin films were prepared at room temperature and deposited onto various substrates (Si, SiO2/glass, and glass). The structural, morphological, and optical characterization was performed by the following techniques: X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Energy-dispersive X-ray (EDX) spectroscopy of ITO films was carried out using a Phenom ProX scanning electron microscope (Thermo Fisher Scientific, Shanghai, China) with special detectors at an accelerating voltage of 15 kV. This EDX mode with an accelerating voltage of 15 kV is adequate for the study of ITO films with a thickness of 180 nm [32][33][34][35]. X-ray diffraction analysis (XRD) was performed to determine the phase composition of the thin films.…”
Section: Methodsmentioning
confidence: 99%
“…Energy-dispersive X-ray (EDX) spectroscopy of ITO films was carried out using a Phenom ProX scanning electron microscope (Thermo Fisher Scientific, Shanghai, China) with special detectors at an accelerating voltage of 15 kV. This EDX mode with an accelerating voltage of 15 kV is adequate for the study of ITO films with a thickness of 180 nm [32][33][34][35]. X-ray diffraction analysis (XRD) was performed to determine the phase composition of the thin films.…”
Section: Methodsmentioning
confidence: 99%
“…ITO sheet resistance, however, will rise with heating, resulting in a higher series resistance in the finished product. It is demonstrated that FTO has a number of advantages over ITO, including cost [12]. There are many compound materials for example 𝐶𝑠 2 𝑇𝑖𝐵𝑟 6 , 𝐶𝑠 2 𝑇𝑖𝐼 1 𝐵𝑟 5 , 𝐶𝑠 2 𝑇𝑖𝐼 2 𝐵𝑟 4 , 𝐶𝑠 2 𝑇𝑖𝐼 3 𝐵𝑟 3 , 𝐶𝑠 2 𝑇𝑖𝐼 4 𝐵𝑟 2 , 𝐶𝑠 2 𝑇𝑖𝐼 5 𝐵𝑟 1 , and 𝐶𝑠 2 𝑇𝑖𝐼 6 which are used in perovskite solar cell currently [13].…”
Section: R T I C L E I N F O Abstractmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] ZnO thin films are processed using methods such as chemical vapor deposition, 8 spray pyrolysis, 9 thermal evaporation, 10 r.f. magnetron sputtering, 11,12 and sol-gel method. [13][14][15] The sol-gel is a low cost deposition method which offers the possibility to obtain oxide films with thickness of nanometric scale, with controlled stoichiometry, good reproducibility, uniformity and doping.…”
Section: Introductionmentioning
confidence: 99%